Formal safety versus real safety: Quantitative and qualitative approaches to safety culture - Meliá, J. L.; Silva, S. A.; Fugas, C. S. (11th International Probabilistic Safety Assessment and Management Conference and the Annual European Safety and Reliability Conference 2012, PSAM11 ESREL 2012, 2012)
Increasingly, many large companies claim to have a serious safety commitment, and they show good or excellent accident records. However, this positive phenomenon is compatible with a formal and image-based approach to safety. This paper presents an in-depth analysis of safety culture in a continuous processing construction plant, focusing on the differences between formal safety and real safety. A sample of 96 employees answered a specific safety culture questionnaire, and 31 participated in personal in-depth safety culture interviews. Sample encompasses main company employees (27.37%), subcontracted companies' employees (26.32%), main company supervisors and middle managers (18.95%), subcontracted supervisors (6.32%) and main company managers (21.05%). This sample covers 90% of the main company's population and 30% of the population of the stable subcontracted companies. Results reveal key issues in safety culture assessment. The statistical analysis of the safety culture questionnaire shows a company with an outstanding safety culture. However, this in-depth study also contributes qualitative data stemming from direct observation and semi-structured interviews. Qualitative data indicate some important safety weaknesses and future targets for safety culture improvement. The contrast between the traditional quantitative data and the qualitative data shows how quantitative data by itself, even in the best conditions of sincerity and commitment, can hide important risks and safety social processes and depict a superficial or distorted view of safety culture.